A Suspected Case of Lyme Borreliosis in a Dog from Belgium - Marina Gatellet; Sébastien Vanderheyden; Michel Abee; Łukasz Adaszek; Marie Varloud (Case Reports in Veterinary Medicine, 2019)
A 5-year-old Jack Russell Spaniel was presented in December 2017 to his veterinarian in Belgium for sudden weakness, reluctance to move, and pain. Blood analysis showed no deviations and serum increased levels of B. burgdorferi s.l. antibodies were detected. The dog recovered a few days after the onset of doxycycline treatment. This case illustrates the possible relationship between tick-borne diseases and orthopedic problems.